Overview of systematic reviews on the most common sports injuries - Manca Zupančič; Jan Marušič (Exercise and Quality of Life)
The frequency and nature of sports injuries depend primarily on the specific sport that an individual play. In this article we review systematic reviews to identify and highlight the most prevalent injuries in basketball, football, volleyball, ice hockey, rugby, and handball. We collected data on the prevalence rates of the most common injuries across these sports, revealing that the most common injuries are lateral ankle sprains, concussions, hamstring strains, quadriceps strains, and various internal knee derangements. Notably, the majority of these injuries affect the lower extremities, which are under the most stress during athletic activities. We also provide insights into preventive measures for the three most common injuries. This compilation of data from different sports will prove valuable to kinesiologists, coaches, and sports professionals, helping them to develop comprehensive training programs aimed at preventing injury and improving overall athletic performance.